Merits of Industrial Clustering: Case of Date’s Industry of Iran - Jamalizadeh, Azam; Sorooshian, Shahryar (Romanian Society for Quality Assurance - SRAC, 2017)
Significance of industrial development made many countries consider the formation and strengthening of small and medium industries of industrial fields, in form of cluster as regional industrial development strategy, and utilize it as employment strategy which is able to improve competition abilities of enterprises and so to enhance their export potentials. Above 90 percent of Iran industries are formed by small and medium enterprises, and based on identified properties of industrial clusters in different regions, cluster development is one of the appropriate and effective patterns for business expansion. Considering the importance of date production in Iran, can be said that development of date industrial cluster has a lot of positive impacts in economic, industrial, social and environmental fields. In this study, by using the technique of DEMATEL, 7 major effective criteria on operation of date industrial cluster including 4 operational features, and 3 sufficiency features were recognized and extracted under supervision of the experts and based on the most practical choices which are compatible with the environment of practical structures of industrial clusters. Results of this research show that networking feature has its priority among practical criteria, export feature includes a high influence taking rate, and feature of cluster enterprises has the most effectiveness and interaction with the other studied criteria. This study indicates that using partnership and networking approach is one of the appropriate ways to solve problems of clusters and is operational for other local and regional clusters.